Counseling on the Role of Working Mothers in Exclusive Breastfeeding in the New Village of Ladang Bambu Medan Tuntungan in 2021 - Dessy Anggreini; Sari Rahma Fitri (Science Midwifery, 2021)
The purpose of this study was to determine the effect of health education with demonstrations and videos on the knowledge of female students/adolescents about BSE examinations in the Ladang Bambu Village, Medan Tuntungan District. And the activities carried out were to increase students' knowledge about BSE examinations in the Ladang Bambu Village, Medan Tuntungan District. Increasing the influence of health education knowledge with demonstration and video methods on adolescent knowledge in the Ladang Bambu Village, Medan Tuntungan District. The results of the research are To achieve the objectives of the above activities, activities were carried out including the delivery of material about the importance of early detection of the breast itself by doing BSE,